Claiming Belonging : Muslim American Advocacy in an Era of Islamophobia - Cury, Emily (Book collections on Project MUSE., 2021)
"This book examines how Muslim American organizations have sought to access and influence the US political system as a minority group and, in the process, engage in constructing a Muslim American political identity"--